Evaluating the macroprudential stance in a growth-at-risk framework - Dominic Cucic; Ianna Georgieva Yordanova; Niels Framroze Møller; Simon Gade Søndergaard (Danmarks Nationalbank, 2022)
The ultimate objective of macroprudential policy is to contribute to financial stability by curbing the build-up of systemic risks and alleviating negative outcomes for the economy should risks materialize . Measuring and communicating whether policy goals are achieved is challenging, as financial crises are rare and risks are often only measurable in case they materialize. The memo outlines how growth-at-risk can be used to illustrate the objectives of macroprudential policy.
Keywords: 330; Finanzmarktaufsicht; Systemrisiko; Finanzsystem; Finanzkrise; Wirkungsanalyse; Dänemark